The double role of ethnic heterogeneity in explaining welfare-state generosity - Markus Jäntti; Gerald Jaynes; John E. Roemer (Luxembourg Income Study (LIS), 2014)
Based on theoretical models of budget-balanced social insurance and individual choice, we argue that in addition to the well-known empathy mechanism whereby ethnic heterogeneity undermines sentiments of solidarity among a citizenry to reduce welfare generosity, population heterogeneity affects the generosity of a polity's social insurance programs through another distinct mechanism, political conflict. Ethnic heterogeneity likely intensifies political conflict and reduces welfare generosity because heterogeneity of unemployment risk makes it more difficult to achieve social consensus concerning taxbenefit programs. Utilizing two separate regression analyses covering highly diverse polities, the 50 U.S. states and District of Columbia (CPS data), and 13 OECD countries (LIS data), we find strong evidence that empirically distinct empathy and political conflict effects on unemployment insurance programs characterize contemporary politics. Our findings suggest existing analyses of the negative relationship between ethnic heterogeneity and the size of the welfare state likely over- or underestimate the empathy effect. For example, perhaps surprisingly, had our analysis of US data omitted a measure of unemployment dispersion, the negative effect of ethnic fractionalization would have been underestimated.
Keywords: H53; 330; political economy; welfare state; social insurance; ethnic fractionalization